The Role of Organizational Members in Entrepreneurship-Based Vision and Mission Innovation: A Study on Islamic Boarding Schools - Ghafar, Muhammad; Sujatnika, Dadang Ahmad; Sutarman, Adang (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aims to analyze the role of organizational members in entrepreneurship-based vision and mission innovation in Islamic boarding schools. This study uses a qualitative method with a case study approach. The Raudhatul Ulum Islamic Boarding School Lumajang, East Java, was used as a research site. Data collection techniques used three techniques: interviews, non-participant observation, and documentation studies. The results showed that the Islamic boarding school Raudhatul Ulum Lumajang applied management theory to formulate and determine Kyai's vision, namely initiating and agreeing on a vision and mission, identifying organizational mandates, and establishing a compelling organizational vision. Recommendation of research findings so that other Islamic Education Institutions, especially Islamic boarding schools, can involve the role of organizational members in determining the vision and mission of the institution being developed